Integrating Life Cycle Thinking and Extended Producer Responsibility into Industrial Symbiosis: A Review of Circular Economy Approaches - Erzen, Buket; Deni?z, Şermin; Aydoğmuş, Ercan; Kar, Filiz; Arslanoğlu, Hasan (Springer Nature, 2026)
The growing adoption of circular economy (CE) principles and industrial symbiosis (IS) has attracted increasing attention across a wide range of engineering disciplines, including chemical, materials, mechanical, and polymer engineering. While existing studies have explored CE and IS from technical and sector-specific perspectives, the systematic integration of life cycle thinking and extended producer responsibility (EPR) into industrial business models remains fragmented in the literature. This study presents a structured review of academic research at the intersection of CE, IS, life cycle approaches, and EPR, with a particular focus on end-of-life (EOL) responsibility and circular value chain formation. Rather than proposing fully operational frameworks, the paper synthesizes conceptual and empirical studies to identify key enabling mechanisms, transition pathways, and persistent challenges in implementing IS-based circular practices across and within industrial sectors. The review highlights how life cycle approaches and producer responsibility can jointly support resource recovery, waste reduction, and long-term collaboration among industrial actors. By clarifying conceptual linkages and governance implications, the study contributes to a more coherent understanding of how CE principles can be operationalized in engineering contexts and provides orientation for researchers, policymakers, and practitioners seeking to support the transition from linear to circular industrial systems. © The Author(s), under exclusive licence to Springer Nature Switzerland AG 2026.
Keywords: Circular economy; Circular value chains; End-of-life management; Extended producer responsibility; Industrial symbiosis; Life cycle thinking